2015
DOI: 10.7763/joebm.2015.v3.175
|View full text |Cite
|
Sign up to set email alerts
|

The Demographic Variables and Emotional Intelligence as Correlates of Work Values: A Cross-Cultural Examination towards Organizational Change

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
0
15
1
1
Order By: Relevance
“…Apibrėžtos akademinės paieškos šiuo klausimu vykdomos ir Lietuvos vadybos mokslo pasaulyje (Lekavičienė, Remeikaitė, 2002;Lekavičienė, Remeikaitė, 2004;Bagdonas, 2012;Ramanauskas, 2012;2013 ir kt.). Lygia greta ieškoma ir emocinio intelekto naudos, praktinio pritaikymo galimybių (Barling, Slater, Kelloway, 2000;Bourey, Miller, 2001;Lekavičienė, Remeikaitė, 2004;Butler, Chinowsky, 2006;Roy, Fillee, de Timary, 2007;Mikolajczak, Luminet, 2008;Berrocal, Cabello, Castilo, Extremera, 2012;Šimanskienė, Ramanauskas, 2014;Trinidad Sanchez-1 Nunez, Patti, Holzer, 2015;Waqas Chughtai, Latter, 2015;Sergio, Dungca, Ormita, 2015;Alfonso, Zenasni, Hodzic, Ripoll, 2016 ir kt.). Be to, manytina, kad neužbaigta ir emocinio intelekto matavimo modelio bei procedūrų paieška (Petrides, Furnham, Frederickson, 2004;Petrides, 2011;Shao, Doucet, Caruso, 2014 ir kt.…”
Section: įVadasunclassified
“…Apibrėžtos akademinės paieškos šiuo klausimu vykdomos ir Lietuvos vadybos mokslo pasaulyje (Lekavičienė, Remeikaitė, 2002;Lekavičienė, Remeikaitė, 2004;Bagdonas, 2012;Ramanauskas, 2012;2013 ir kt.). Lygia greta ieškoma ir emocinio intelekto naudos, praktinio pritaikymo galimybių (Barling, Slater, Kelloway, 2000;Bourey, Miller, 2001;Lekavičienė, Remeikaitė, 2004;Butler, Chinowsky, 2006;Roy, Fillee, de Timary, 2007;Mikolajczak, Luminet, 2008;Berrocal, Cabello, Castilo, Extremera, 2012;Šimanskienė, Ramanauskas, 2014;Trinidad Sanchez-1 Nunez, Patti, Holzer, 2015;Waqas Chughtai, Latter, 2015;Sergio, Dungca, Ormita, 2015;Alfonso, Zenasni, Hodzic, Ripoll, 2016 ir kt.). Be to, manytina, kad neužbaigta ir emocinio intelekto matavimo modelio bei procedūrų paieška (Petrides, Furnham, Frederickson, 2004;Petrides, 2011;Shao, Doucet, Caruso, 2014 ir kt.…”
Section: įVadasunclassified
“…Studies have demonstrated the significant relationship between demographic and professional characteristics and work values (Aladwan et al , 2016; Sergio et al , 2015; Posner, 2010; Wray-Lake et al , 2011). For example, Aladwan et al (2016) revealed the differences in work values among employees with different educational background and work experience and in different types of business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with these definitions, Ho (2006, p. 11) and Uçanok (2008, p. 157) defined work values as the goals that employees attempt to achieve through working. Wils et al (2011) (Sergio, Dungca & Ormita, 2015). Ros et al (1999) identified four dimensions of work values, namely extrinsic, intrinsic, social and power values.…”
Section: Work Valuesmentioning
confidence: 99%